2010
DOI: 10.1089/neu.2009.1014
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Dynamics in the Acute Phase of Aneurysmal Subarachnoid Hemorrhage: Associations with Disease Severity and Outcome

Abstract: The purpose of this study was to assess cortisol dynamics in the acute phase after aneurysmal subarachnoid hemorrhage (SAH) and to set the parameters of cortisol release in relation to the severity of illness and outcome. In 22 consecutive patients with aneurysmal SAH, cortisol, corticosteroid binding globulin, interleukin-6, and adrenocorticotrophic hormone were measured immediately after hospital admission (t(0)), 7 days (t(1)) later, and at least 14 days later (t(2)). Additionally, diurnal profiles of corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…The majority of them were prospective single-centre studies (N = 15, 75 %), two were prospective multi-centric Criteria for diagnosis of endocrine abnormality differed widely, and included both basal hormone levels and stimulation tests ( Table 2). Five authors studied just a single hormonal axis (somatotropic [10], or adrenal axis [13,[26][27][28]) and the remaining studied multiple hormone alterations.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of them were prospective single-centre studies (N = 15, 75 %), two were prospective multi-centric Criteria for diagnosis of endocrine abnormality differed widely, and included both basal hormone levels and stimulation tests ( Table 2). Five authors studied just a single hormonal axis (somatotropic [10], or adrenal axis [13,[26][27][28]) and the remaining studied multiple hormone alterations.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Similar results were described by Pereira et al [15] who demonstrated that hormone deficiency is not significantly associated (p = 0.05) with increased hospitalization or clinical outcome. In opposition, some authors found a significant association between pituitary dysfunction and patients' outcome [11,13]: Lammert et al [24] demonstrated that all patients with neuro-endocrine dysfunction presented impaired clinical outcome (p value = 0.007) and Poll et al [28] found that patients with normal diurnal free serum cortisol had a significantly shorter ICUstay, less complications, and a more favorable outcome (p value = 0.051).…”
Section: Factors Influencing the Prevalence Of Pituitary Disordersmentioning
confidence: 99%
“…The degree of cortisol elevation was not associated with the severity of SAH. In contrast, mixed results of normal cortisol with low or normal levels of ACTH were found by Poll et al [16]. In the latter study, the diurnal variation of free cortisol levels was abnormal in some SAH patients, and correlated with poor outcome and longer length of stay compared with those patients with normal diurnal variation.…”
Section: Incidence Of Hpa Insufficiencymentioning
confidence: 74%
“…Several prospective observational studies have been performed to document the incidence of dysfunction of the HPA axes, primarily through prospective measures of individual hormonal concentrations in the acute and chronic setting (Table 1 [4,[7][8][9][10][11][12][13][14][15][16]). Unfortunately, most studies focus on the chronic setting from 12 to 72 months after SAH.…”
Section: Incidence Of Hpa Insufficiencymentioning
confidence: 99%
“…Several prospective observational studies have been performed to document the incidence of dysfunction of the HPA axis, primarily through prospective measures of individual hormonal concentrations in the acute and chronic setting (Table 1; [4,[7][8][9][10][11][12][13][14][15][16]). Unfortunately, most studies focus on the chronic setting from 12 to 72 months after SAH.…”
Section: Incidence Of Hpa Insufficiencymentioning
confidence: 99%